1989
DOI: 10.1111/j.1524-4725.1989.tb03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Microcystic Adnexal Carcinoma of the Scalp

Abstract: Microcystic adnexal carcinoma (MAC) is a recently described rare adnexal neoplasm showing benign histologic features but a locally aggressive behavior. It has most commonly been reported to occur on the face but it has also been noted in the axilla and buttock. We describe a 41-year-old white male with a 5-year history of MAC on the scalp and treatment by Mohs micrographic surgery. To our knowledge, this is the first case of MAC reported to occur on the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…MAC is generally believed to be the result of the malignant degeneration of pluripotent adnexal keratinocytes capable of differentiation toward both sweat ducts and hair follicles. 14 The central face is the most common location for this tumor, however, other reported locations include the scalp, 9,11,15,16 axilla, 1 neck, 7 chest, 9 buttocks, 1 back, 17 perianal skin, 12 and sole of the foot. [4][5][6][7][8][9] This tumor is typically seen in middle-aged to elderly persons; however, reported ages at presentation have ranged from 11 years old 10 to 86 years old.…”
Section: Discussionmentioning
confidence: 99%
“…MAC is generally believed to be the result of the malignant degeneration of pluripotent adnexal keratinocytes capable of differentiation toward both sweat ducts and hair follicles. 14 The central face is the most common location for this tumor, however, other reported locations include the scalp, 9,11,15,16 axilla, 1 neck, 7 chest, 9 buttocks, 1 back, 17 perianal skin, 12 and sole of the foot. [4][5][6][7][8][9] This tumor is typically seen in middle-aged to elderly persons; however, reported ages at presentation have ranged from 11 years old 10 to 86 years old.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Although the majority of cases appear on the face, MAC occurrences on the scalp, [3][4][5][6][7][8][9][10][11][12][13] tongue, 14 neck, 6,7,15 axilla, 4,6,16-18 trunk, 2,7,18-23 upper extremities, 2,18,20,24 vulva, 7,25 buttocks, 26 and lower extremities 18,20,23,27,28 have been described. Yoon and colleagues detailed a unique occurrence within a teratoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Chow et al (19) reported that 40-60% of patients experienced one or more local recurrences following standard wide local excision. MMS is a therapeutic approach for skin cancer removal that aims to achieve the highest possible cure rates, while minimizing the size of the wound and consequent distortions.…”
Section: Discussionmentioning
confidence: 99%